Cooling discourses, agnosis and environmental harm - Monod de Froideville, Sarah (Crime, media, culture, 2022)
Critical scholars consider a lack of action around issues of environmental harm a ?product of persuasion? by way of various forms of denial, downplay and spin on behalf of elite parties invested in maintaining a neo-liberal social and economic status quo. This paper introduces to this body of work the concept of ?cooling discourses? in relation to two cases of environmental harm in the New Zealand (NZ) context. Cooling discourses are employed to settle concerns about harmful activity that are gathering momentum through acknowledging the harm and appearing to address the activity in some manner. Cooling discourses are temporary stupefying discourses that facilitate a state of ignorance, or agnosis so that harmful activity can continue or resume unopposed.